The attitudes of medical students to autopsy - İNANICI, MEHMET AKİF (My University, 2000)
To assess the attitudes of medical students to autopsy, 6th year students in the Medical Schools located in Istanbul, Edirne and Bursa in Turkey were asked to participate in a questionnaire. In the questionnaire, the main questions were on the number of autopsies they had attended, the number of autopsies they had participated in, their reaction to the first autopsy, whether they felt the conditions were adequate or not and what would their objectives be upon deciding to perform an autopsy. In the evaluation, it was detected that most of the participants had attended an autopsy, only a minority had participated in autopsy and most of them felt uncomfortable and inadequate on performing autopsy. The results were discussed with respect to the literature.
Keywords: Adult; Female; Humans; Surveys and Questionnaires; Turkey; Male; Health Knowledge, Attitudes, Practice; Attitude of Health Personnel; Clinical Competence; Self-Assessment; Students, Medical; Autopsy